Model Kemitraan Islam Melalui Collective Enterprise untuk Keberlanjutan Usaha Pangkas Rambut - Helmi Mahmud; Fahrurrozi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
A company must have a desire to achieve the goals that have been targeted, but in an uncertain situation a company must make decisions that can be detrimental to its business and must continue the company's vision and mission, so that the business continues to be sustainable without experiencing considerable losses, then a company must cooperate with other companies such as partnering with the Collective Enterprise system that based on Islam so that companies participating in the Collective Enterprise feel not disappointed and foster a high sense of solidarity, a Collective Enterprise in a barber business partnership has a characteristic that distinguishes it from other businesses, when doing a business will not be able to stand alone but still needs the support of the business system which has easier system support in the sustainability of the business, In this sustainability, business partnerships are very much considered so that they use Islamic partnerships because Islam is the religion that Rahmatan Lil Alamin is considered to be.